EVALUASI KEBIJAKAN OPERASI PANGAN RIAU MAKMUR ( OPRM ) DI KABUPATEN PELALAWAN TAHUN 2010-2013 - Zamira Ulfa; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Rice the staple food of the people of Indonesia, especially in Riau, it formed a policy for Improved Rice production in order to increase rice production in Riau, the Riau prosperous Food Operations program covering Increased Investment Index IP 100 - IP 200, Rehabilitation of Abandoned Rice Fields and New Print. At this time the author focuses on the research Pelalawan. This study aims to identify the implementation OPRM in Pelalawan and to identify factors - factors that affect the implementation of OPRM.The research method used is qualitative descriptive , which explains the problem in detail with the correct data retrieval and accurate as well as see the conditions that occurred during the program is realized.The results of this study concluded that the factors supporting the implementation OPRM in Pelalawan is the human resources support, especially support the agricultural land in Kuala Kampar, POSKO Coordination run very effectively which is characterized by frequent execution coordination meetings, running His organization structure, as well as the budget available and the direct supervision of spaciousness. Can not be separated from the presence of inhibiting factors that affect the implementation of the transfer of functions OPRM the land, not optimal irrigation networks, water shortages and inadequate road infrastructure, particularly rice production center in Kuala Kampar.Key Words : Evaluation, OPRM, Pelalawan